Beyond borders: investigating the impact of the 2023 conflict in Gaza on generalized anxiety disorders and associated somatic symptoms and wellbeing among the Kuwait population: a global call for public intervention programs - Musaed Z. Alnaser; Hamad Alhamad; Naser Alotaibi; Nadia Alhamdan; Fahad Manee (Frontiers in Public Health)
PurposeArmed conflicts can lead to devastating psychological health issues within and around conflict zones. Generalized anxiety disorder, associated somatic symptoms, and wellbeing were examined among the Kuwait population during the Gaza Conflict in 2023, in addition to exploring the provoking factors.MethodsA descriptive, correlational cross-sectional design was used in this study. An online survey was conducted to collect information from people living in Kuwait during the Gaza Conflict. Data were collected between November 20 and November 27, 2023. The generalized anxiety disorder scale (GAD-7), a modified patient health questionnaire (mPHQ-15), and the World Health Organization – Five (WHO-5) were used to examine self-reported anxiety, somatic symptoms, and wellbeing among the study participants. Spearman’s correlation and chi-squared tests were used to determine the relationships between anxiety, somatic symptoms, and wellbeing, and to capture the instigating factors.ResultsThis study included 1979 participants living in Kuwait during the Gaza conflict period. GAD-7 and mPHQ-5 final scores were moderate (μ = 10.20 ± 4.48; μ = 11.12 ± 6.39), and WHO-5 final score was fair (μ = 53.35 ± 21.82). Spearman’s correlation showed a large positive correlation between the GAD-7 and mPHQ-15, r(1977) = 0.52, p < 0.0001, a medium negative correlation between the GAD-7 and WHO-5, r(1977) = −0.36, p < 0.0001, and a medium negative correlation between the mPHQ-15 and WHO-5, r(1977) = −0.27, p < 0.0001. Spearman’s correlation showed a small positive correlation between the GAD-7 and current feelings of insecurity, r(1977) = 0.246, p < 0.0001, and medium positive correlation with future fears, r(1979) = 0.292, p < 0.0001.ConclusionThe Gaza conflict impacted the psychological health of the Kuwait population, who shared geographical, geocultural, and geopolitical factors with those in the conflict zone. A global call to address mental health intervention programs for the public in and around conflict zones is a priority.